Deep Tissue Wavefront Estimation for Sensorless Aberration Correction - Ibrahimovic Emina (MATEC Web of Conferences, 2015)
The multiple light scattering in biological tissues limits the measurement depth for traditional wavefront sensor. The attenuated ballistic light and the background noise caused by the diffuse light give low signal to noise ratio for wavefront measurement. To overcome this issue, we introduced a wavefront estimation method based on a ray tracing algorithm to overcome this issue. With the knowledge of the refractive index of the medium, the wavefront is estimated by calculating optical path length of rays from the target inside of the samples. This method can provide not only the information of spherical aberration from the refractive-index mismatch between the medium and biological sample but also other aberrations caused by the irregular interface between them. Simulations based on different configurations are demonstrated in this paper.